PENERAPAN MODEL PEMBELAJARAN THE “SAS” TEAM UNTUK MENINGKATKAN KEMAMPUAN SISWA KELAS VIII DALAM MENULIS TEKS FUNGSIONAL KHUSUS - Abdul Hamid (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
This classroom action research was intended to find out the information about the application of The “SAS” Team learning model to increase the students’ability of grade VIII in writing the short functional text at SMP Negeri 1 Banjarmasin. This research was conducted in grade VIII B with 32 students. This research was conducted in two cycles with the four steps: planning, acting, observing and reflecting. The quantitative data of the students’learning achievement were obtained through test and the data of achievement per aspect were collected through the analysis result of the students’answer sheets. The qualitative data of the students’learning activities were collected through simple observation sheet. The result of this study showed that the application of The “SAS” Team learning model was able to increase the students’ability of the grade VIII in writing the short functional text at SMP Negeri 1 Banjarmasin with the achievement 96,87% students achieved the Minimum Criteria of Mastery Learning (76) and the average score is 86.82.